HEMO2life® improves renal function independent of cold ischemia time in kidney recipients: A comparison with a large multicenter prospective cohort study. Issue 4 (24th December 2021) - Le Meur, Yannick; Delpy, Eric; Renard, Felix; Hauet, Thierry; Badet, Lionel; Rerolle, Jean Philippe; Thierry, Antoine; Büchler, Matthias; Zal, Franck; Barrou, Benoit
Abstract: Background: M101 is an extracellular hemoglobin isolated from a marine lugworm and is present in the medical device HEMO2 life®. The clinical investigation OXYOP was a paired kidney analysis ( n = 60) designed to evaluate the safety and performance of HEMO2 life® used as an additive to preservation solution in renal transplantation. The secondary efficacy endpoints showed less delayed graft function (DGF) and better renal function in the HEMO2 life® group but due to the study design cold ischemia time (CIT) was longer in the contralateral kidneys. Methods: An additional analysis was conducted including OXYOP patients and patients from the ASTRE database ( n = 6584) to verify that the decrease in DGF rates observed in the HEMO2 life® group may not be due solely to the shorter CIT but also to HEMO2 life® performance. Kaplan–Meier estimate curves of cumulative probability of achieving a creatinine level below 250 µmol/L were generated and compared in both groups. A Cox model was used to test the effect of the explanatory variables (use of HEMO2 life® and CIT). Finally, a bootstrap strategy was used to randomly select smaller samples of patients and test them for statistical comparison in the ASTRE database. Results: Kaplan–Meier estimate curves confirmed the existence of a relation between DGF and CIT and Cox analysis showed a benefit in the HEMO2 life® group regardless of the associated CIT. Boostrap analysis confirmed these results. Conclusions: The present study suggested that the better recovery of renal function observed among kidneys preserved with HEMO2 life® in the OXYOP study is a therapeutic benefit of this breakthrough innovative medical device. Abstract : M101 is an extracellular hemoglobin isolated from a marine lugworm and present in the medical device HEMO2 life® already tested in the clinical investigation OXYOP to evaluate its safety and performance in renal transplantation. New statistical analyses were conducted including OXYOP patients and patients from the ASTRE database. The study confirmed that the better recovery of renal function observed among kidneys preserved with HEMO2life® in the OXYOP study is a clear therapeutic benefit of this breakthrough innovative medical device.